(untitled) (The International Journal of Engineering & Information Technology (IJEIT), 2024)
In this study, the energy consumption by the process of steel billet reheating in an industrial steel reheat furnace at the Libya Iron and Steel Company (LISCO) is considered. It is known that in the steel industry, one of the processes requiring the most energy is the process of reheating the steel prior to hot rolling. A comprehensive mass and heat balance was performed on the furnace, taking into account all actual entering and exiting furnace parameters. Furnace thermal efficiency was found to be low and heat losses from different areas of the furnace were considerable.